2020
DOI: 10.1093/mnras/staa571
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia DR2 parallax zero-point: hierarchical modelling of red clump stars

Abstract: The systematic offset of Gaia parallaxes has been widely reported with Gaia's second data release, and it is expected to persist in future Gaia data. In order to use Gaia parallaxes to infer distances to high precision, we develop a hierarchical probabilistic model to determine the Gaia parallax zero point offset along with the calibration of an empirical model for luminosity of red clump stars by combining astrometric and photometric measurements. Using a cross-matched sample of red clump stars from the Apach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
7
41
1
Order By: Relevance
“…Regarding the Gaia DR2 parallaxes, as reported by Lindegren et al (2018) and confirmed by several other works (Chan & Bovy 2020;Riess et al 2018;Schönrich et al 2019;Stassun & Torres 2018;Zinn et al 2019), there is a zero-point offset that needs to be considered. For the remainder of this paper, we adopt the global mean value of 29 µas for all the clusters (in the sense that the Gaia parallaxes are too small) reported by Lindegren et al (2018), with the exception of NGC 6811, for which we adopt the Kepler field 53 µas value from Zinn et al (2019).…”
Section: Gaia Dr2 Datamentioning
confidence: 51%
“…Regarding the Gaia DR2 parallaxes, as reported by Lindegren et al (2018) and confirmed by several other works (Chan & Bovy 2020;Riess et al 2018;Schönrich et al 2019;Stassun & Torres 2018;Zinn et al 2019), there is a zero-point offset that needs to be considered. For the remainder of this paper, we adopt the global mean value of 29 µas for all the clusters (in the sense that the Gaia parallaxes are too small) reported by Lindegren et al (2018), with the exception of NGC 6811, for which we adopt the Kepler field 53 µas value from Zinn et al (2019).…”
Section: Gaia Dr2 Datamentioning
confidence: 51%
“…The presence of a zero-point offset in the parallaxes published in Gaia DR2 has been established both in papers describing Gaia data (Lindegren et al 2018) and by comparison with independent distance determinations (e.g., see Riess et al 2018;Stassun & Torres 2018;Khan et al 2019;Hall et al 2019;Zinn et al 2019;Schönrich et al 2019;Chan & Bovy 2020). Such an offset is largely due to a degeneracy between the parallax and the basic-angle variation of the Gaia satellite.…”
Section: Caveats and Prospectsmentioning
confidence: 92%
“…The resulting uncertainty of the intercepts is ∼0.1 mag, and it was added quadratically to the systematics. We converted the reddening free magnitudes into distances using the distance modulus and assuming an absolute magnitude of M K s = −1.59 ± 0.04 for RC stars, which was computed by averaging over the values obtained by Groenewegen (2008), Hawkins et al (2017), and Chan & Bovy (2020). The uncertainty corresponds to the standard deviation of the measurements.…”
Section: Reddening Vector and Distancesmentioning
confidence: 99%